Development of low-emission hydrogen energy in Egypt's energy industry - Patryk Chmielarz; Alan Beroud (Przegląd Komunikacyjny)
Abstract: The article focuses on the analysis of one of the key area of the energy system, which is energy from renewable sources. The authors focused on considerations covering the Egyptian energy sector. Possibilities and limitations of the Egyptian energy sector in the renewable energy segment were presented. The attention has been put on the benefits that may occur from the cooperation agreements signed by Egypt in field of hydrogen based energy. The advantages of the solutions taken in opposition to the costs of hydrogen energy were presented as a significant but acceptable disadvantage in terms of the need to take measures to increase the share of renewable energy sources in Egypt. Cost analysis was performed on examples, based on market forecasts. The article takes into account the stability defined as the two decades long stabilization of the Egyptian energy sector, which translates into the implementation of the adopted plans and assumptions by this country.